80 Jahre Motorisierung in Stadt und Land. Fallstudie Nordrhein-Westfalen. - Scheiner, Joachim (Deutscher Verkehrs-Verl., 2010)
Die historische Entwicklung der Motorisierung ist von Verkehrspolitikern in politischer, sozialer, ökonomischer und technischer Sicht intensiv erforscht worden. Dies gilt jedoch nicht für deren räumliche Differenzierung. Heute ist die Motorisierung in Städten bekanntlich deutlich geringer als in suburbanen und ländlichen Räumen. Dies war jedoch nicht immer so. Der Beitrag untersucht räumliche Struktur der Motorisierung in Nordrhein-Westfalen und seinen Vorgängerregionen seit 1928.

Historical trends in the motorisation rate have been studied intensively by transport historians in their political, social, economic and technical facets. However, this is not true for long-term spatial differences in these trends. Today, the motorisation rate is known to be considerably lower in cities than in suburban and rural areas: This has not been so from the beginning. The paper studies spatial structures in motorisation in North Rhine-Westphalia and its predecessor regions for the period 1928 to 2008. The results show that only from the 1970s the cities were overtaken by rural areas in terms of motorisation. In some cases there are still some rural areas with a relatively low motorisation. What is more, there are considerable differences between the Ruhr area and other, more wealthy cities.
80 years of motorisation in urban and rural areas.
Keywords: Verkehr; Verkehrsentwicklung; Motorisierung; Individualverkehr; Personenkraftwagen; Ländlicher Raum; Mobilität; Raumstruktur; Verkehrsgeschichte